2001
DOI: 10.1152/physiolgenomics.2001.6.2.91
|View full text |Cite
|
Sign up to set email alerts
|

Rat mitochondrial ATP synthase ATP5G3: cloning and upregulation in pancreas after chronic ethanol feeding

Abstract: Individuals with chronic excessive alcohol ingestion are put at the risk of acute and chronic pancreatitis. Underlying molecular mechanisms are unknown. Differential gene expression in the pancreas was profiled using mRNA differential display by comparison between control and ethanol-consuming rats. Male Wistar rats were fed with diets containing 6.7% (vol/vol) ethanol for 4 wk. A cDNA tag that was overexpressed in the pancreas of rats fed ethanol was isolated. A 723-bp cDNA was cloned from a rat pancreatic cD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 47 publications
0
31
1
2
Order By: Relevance
“…One of the up-regulated gene, ATP synthase H1 transporting, isoform 3 (ATP5G3), plays a role in the generation of a mitochondrial membrane potential by hydrolysis of ATP and may correlate with the altered potential of AMRtreated cells in vitro. 43,44 Another major apoptotic gene, caspase 3, was up regulated 2.3-fold, 5.1-fold and 6.3-fold by 2, 5 and 10 mg/ kg AMR treatment in xenograft tumors. Apart from these direct effects, several transcription factors (PTMA, HCFC1, NFE2L3, DHX9, TAF12, HOXD3) and transcription regulatory proteins (MID1, PTTG1, RB1, CDK2AP1, MTA2, SP100) were also upregulated by AMR.…”
Section: Discussionmentioning
confidence: 95%
“…One of the up-regulated gene, ATP synthase H1 transporting, isoform 3 (ATP5G3), plays a role in the generation of a mitochondrial membrane potential by hydrolysis of ATP and may correlate with the altered potential of AMRtreated cells in vitro. 43,44 Another major apoptotic gene, caspase 3, was up regulated 2.3-fold, 5.1-fold and 6.3-fold by 2, 5 and 10 mg/ kg AMR treatment in xenograft tumors. Apart from these direct effects, several transcription factors (PTMA, HCFC1, NFE2L3, DHX9, TAF12, HOXD3) and transcription regulatory proteins (MID1, PTTG1, RB1, CDK2AP1, MTA2, SP100) were also upregulated by AMR.…”
Section: Discussionmentioning
confidence: 95%
“…Such mitochondrial inhibition appears to provoke compensatory protective measures in the cell, including an upregulation of mitochondrial ATP synthase, observed after both cerulein hyperstimulation and chronic alcohol exposure. 85 The importance of ATP depletion for pancreatic acinar cell fate is further underscored by experiments in which addition of ATP to the cell interior, administered via a patch pipette, was able to reverse the detrimental Ca 2 þ signals induced by alcohol metabolites. For example, FA-induced sustained cytosolic Ca 2 þ rises, via the release from ER Ca 2 þ stores and subsequent Ca 2 þ entry, were completely abolished in cells receiving supplementary ATP, whereas control cells produced large, sustained elevations of cytosolic Ca 2 þ (Figure 4) 12 that cause cellular necrosis.…”
Section: 75mentioning
confidence: 99%
“…Ethanol-induced mitochondrial dysfunction was suggested to account for pancreatic steatosis, but again results were conflicting. After long-term ethanol administration, some authors observed pancreatic mitochondrial damage such as swelling and formation of giant mitochondria, fragmentation of the internal membranes and damaged cristae in the rat [32,[46][47][48][49], others did not report these alterations [36,45]. In another study with Lieber-DeCarli ethanol-fed rats, Wilson et al [50] isolated functional mitochondria from the rat pancreas and measured respiratory parameters.…”
Section: Effects Of Chronic Alcohol Administration In Combination Witmentioning
confidence: 99%